2018
DOI: 10.1021/acscatal.7b03597
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Breaking Scaling Relations in Single-Site Catalysis: Methane to Methanol Conversion by FeIV═O

Abstract: Computational high-throughput screening is an essential tool for catalyst design, limited primarily by the efficiency with which accurate predictions can be made. In bulk heterogeneous catalysis, linear free energy relationships (LFERs) have been extensively developed to relate elementary step activation energies, and thus overall catalytic activity, back to the adsorption energies of key intermediates, dramatically reducing the computational cost of screening. The applicability of these LFERs to single-site c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(172 citation statements)
references
References 133 publications
9
161
2
Order By: Relevance
“…Motivated by similar schemes for computational catalysis screening of bulk metals and alloys, the general approach for HT‐DFT of MOF catalysts can be outlined as follows: Determine a set of catalytic descriptors that can be used to correlate catalytic activity with readily computed quantities, such as those based on adsorption energies, reaction energies, or electronic structure properties Identify or construct a dataset of MOF crystal structures to study.…”
Section: General Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by similar schemes for computational catalysis screening of bulk metals and alloys, the general approach for HT‐DFT of MOF catalysts can be outlined as follows: Determine a set of catalytic descriptors that can be used to correlate catalytic activity with readily computed quantities, such as those based on adsorption energies, reaction energies, or electronic structure properties Identify or construct a dataset of MOF crystal structures to study.…”
Section: General Schemementioning
confidence: 99%
“…In contrast with the C—H bond activation step, there is currently no reported universal TS scaling relationship for the step in which the metal site is oxidized. Instead, we consider the extrinsic oxidation reaction energy using N 2 O as the proposed oxidant, defined as normalΔEox=()EMOFnormalO+EnormalN2()EMOF+EN2normalO to determine the thermodynamic favorability of oxidation, as has been done in prior work . Here, E MOF , EnormalN2, and EN2normalO are the electronic energies of the bare MOF (i.e., the reduced state), gas‐phase N 2 , and gas‐phase N 2 O, respectively.…”
Section: Catalytic Descriptors For Oxidative C—h Bond Activationmentioning
confidence: 99%
“…However, a recent computational study by Gani and Kulik who considered about 500 model Fe 2+ compounds for methane oxidation to methanol with N 2 O oxidant reveal important limitations of such the predictive models based on the linear scaling relationship approximation . It was shown that the linear relationship for single site catalyst screening holds only when the geometric parameters of iron are fixed.…”
Section: Lewis Acidity Of Zeolitesmentioning
confidence: 99%
“…were able to model Fe(II) single‐site catalyst (though not FeN x ) for methane hydroxylation, demonstrating that i) the tuning of the ligand field strength yields LFERs and ii) scaffold distortion not only breaks strong linear scaling relations arising from ligand field strength tuning but also alters BEP relations for oxo formation (Figure ). We believe that such approach could be very helpful in rationalising reaction mechanisms on FeN x single‐site catalysts in the future …”
Section: Identification Of Fenx Single Sitesmentioning
confidence: 99%
“… Understanding and Breaking Scaling Relations in Single‐Site Catalysis: Methane to Methanol Conversion by Fe IV =O. Reproduced with permission from . Copyright 2018 American Chemical Society.…”
Section: Identification Of Fenx Single Sitesmentioning
confidence: 99%